Major government customers and loan contract terms - COHEN, Daniel A. (Institutional Knowledge at Singapore Management University, 2022)
We examine the relation between the presence of U.S. government as a major customer and a supplier firm’s loan contract terms, using major corporate customers as a benchmark. We find that firms with major government customers are associated with fewer covenants and a lower likelihood of having performance pricing provisions in their loan contracts. In contrast, we do not find such associations for firms with major corporate customers. Further, we find no evidence that the existence of major government customers is related to the supplier firm’s loan spread, security, or maturity. We conjecture that lenders benefit from the stricter monitoring of the government as a major customer and thus use fewer covenants and performance pricing provisions when lending to firms with major government customers than when lending to those with major corporate customers. We provide evidence consistent with this conjecture.